207k views
2 votes
Simplify: 3(8x - 5) + 10(10 - x)

2 Answers

3 votes

3(8x−5)+10(10−x)

=(3)(8x)+(3)(−5)+(10)(10)+(10)(−x)

=24x+−15+100+−10x

=24x+−15+100+−10x

=(24x+−10x)+(−15+100)

=14x+85 <- ANSWER

User Caxapexac
by
5.4k points
3 votes

Answer:

Explanation:

3(8x - 5) + 10(10 - x) = 3*8x - 3*5 + 10*10 - 10* x

= 24x - 15 +100 -10x

= (24x -10x ) -15 +100

= 14x + 85

When two terms are in different sign, then subtract and put the bigger number's sign in the result

Here distribution property is used:

a*(b+c) = a*b + a*c

a*(b-c ) = a*b - a*c

User Ellbar
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.